Hydrogen Sulfide Releasing Aspirin, ACS14, Attenuates High Glucose-Induced Increased Methylglyoxal and Oxidative Stress in Cultured Vascular Smooth Muscle Cells - Huang, Qian (Public Library of Science, 2014)
Hydrogen sulfide is a gasotransmitter with vasodilatory and anti-inflammatory properties. Aspirin is an irreversible cyclooxygenase inhibitor anti-inflammatory drug. ACS14 is a novel synthetic hydrogen sulfide releasing aspirin which inhibits cyclooxygenase and has antioxidant effects. Methylglyoxal is a chemically active metabolite of glucose and fructose, and a major precursor of advanced glycation end products formation. Methylglyoxal is harmful when produced in excess. Plasma methylglyoxal levels are significantly elevated in diabetic patients. Our aim was to investigate the effects of ACS14 on methylglyoxal levels in cultured rat aortic vascular smooth muscle cells. We used cultured rat aortic vascular smooth muscle cells for the study. Methylglyoxal was measured by HPLC after derivatization, and nitrite+nitrate with an assay kit. Western blotting was used to determine NADPH oxidase 4 (NOX4) and inducible nitric oxide synthase (iNOS) protein expression. Dicholorofluorescein assay was used to measure oxidative stress. ACS14 significantly attenuated elevation of intracellular methylglyoxal levels caused by incubating cultured vascular smooth muscle cells with methylglyoxal (30 µM) and high glucose (25 mM). ACS14, but not aspirin, caused a significant attenuation of increase in nitrite+nitrate levels caused by methylglyoxal or high glucose. ACS14, aspirin, and sodium hydrogen sulfide (NaHS, a hydrogen sulfide donor), all attenuated the increase in oxidative stress caused by methylglyoxal and high glucose in cultured cells. ACS14 prevented the increase in NOX4 expression caused by incubating the cultured VSMCs with MG (30 µM). ACS14, aspirin and NaHS attenuated the increase in iNOS expression caused by high glucose (25 mM). In conclusion, ACS14 has the novel ability to attenuate an increase in methylglyoxal levels which in turn can reduce oxidative stress, decrease the formation of advanced glycation end products and prevent many of the known deleterious effects of elevated methylglyoxal. Thus, ACS14 has the potential to be especially beneficial for diabetic patients pending further in vivo studies.